Total Quality Management Practices and Supply Chain Management: Understanding Linkages from the Logistics Sector of Pakistan - Muhammad Saad Ameer (SEISENSE Journal of Management, 2018)
The study is an outcome of a conceptual framework that establishes the relationship between the total quality management (TQM) practices and supply chain management (SCM) practices. The six TQM practices have taken from the Malcolm Baldrige National Quality Award (MBNQA). These practices are leadership, strategic planning, customer focus, human resource management, process management, and information analysis. The result is based on the logistics sector in Pakistan. Data is collected from 270 operation manager and top management. Multiple regression analysis is used to derive the results from the collected data. The result shows the strong relationship between the variables. Leadership, strategic planning, customer focus, and human resource management relationship with SCM was found significant. However, process management and information analysis were insignificant relationships with SCM. This study can be used for the implementation of both the systems – TQM and SCM in the organization to drive better results.